2019
DOI: 10.1002/cncr.32495
|View full text |Cite
|
Sign up to set email alerts
|

Inclusiveness and ethical considerations for observational, translational, and clinical cancer health disparity research

Abstract: Background Although general trends in cancer outcomes are improving, racial/ethnic disparities in patient outcomes continue to widen, suggesting disparity‐related shortcomings in cancer research designs. Methods Using convenience sampling, a total of 24 data sources, representing several research designs and 5 high‐burden tumor types, were included for analyses. The percentages of races/ethnicities across each design/tumor type were compared with those of the 2017 US Census data. The authors used a framework b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 59 publications
0
17
0
Order By: Relevance
“…We were unable to account for number of clinical trials open for AYA enrollment during this time period so further work is needed. 40 , 41 Lower Black AYA and overall enrollment in 2014, when the NCI Clinical Trials Network was restructured, may have been secondary to a decrease in the overall number of available trials. As expected, we identified differences in CTT enrollment among the AYAs with those 15–19y enrolling more often than those 20–39y.…”
Section: Discussionmentioning
confidence: 99%
“…We were unable to account for number of clinical trials open for AYA enrollment during this time period so further work is needed. 40 , 41 Lower Black AYA and overall enrollment in 2014, when the NCI Clinical Trials Network was restructured, may have been secondary to a decrease in the overall number of available trials. As expected, we identified differences in CTT enrollment among the AYAs with those 15–19y enrolling more often than those 20–39y.…”
Section: Discussionmentioning
confidence: 99%
“…In a review of 24 data sources conducted in 2017, White individuals were found to be overrepresented compared to other racial/ethnic groups who were consistently underrepresented across all cancer research study designs for 5 high‐burden tumor types. Notably, equitable subject selection was higher in observational studies compared with interventional clinical trials 5 . This echoes the reality that clinical trial recruitment is complex and requires a deeper appreciation of the multiple factors that impact participation of racial/ethnic minorities.…”
Section: Where Do We Stand?mentioning
confidence: 97%
“…Effective measures used to capture relevant information should prioritize the inclusion of minority races that often are under-represented in, for example, large clinical trials to avoid bias. 43 Data sets are the lifeblood of algorithms and statistical modelling on which AI systems are trained. Researchers and clinicians have a duty of care to ensure that the provenance and quality of the data used to train these algorithms are impeccable and curated in compliance with federal regulatory guidelines.…”
Section: Data Acquisition and Data Qualitymentioning
confidence: 99%
“…This requirement should be implicit for the design of AI systems in any surgical specialty with patient recruitment as the first step in the data acquisition process for clinical trials. Effective measures used to capture relevant information should prioritize the inclusion of minority races that often are under‐represented in, for example, large clinical trials to avoid bias 43 …”
Section: Framework For the Development And Adoption Of Ai Systems In mentioning
confidence: 99%